2017
DOI: 10.1007/s00125-017-4422-0
|View full text |Cite
|
Sign up to set email alerts
|

DEVOTE 3: temporal relationships between severe hypoglycaemia, cardiovascular outcomes and mortality

Abstract: Aims/hypothesisThe double-blind Trial Comparing Cardiovascular Safety of Insulin Degludec vs Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) assessed the cardiovascular safety of insulin degludec. The incidence and rates of adjudicated severe hypoglycaemia, and all-cause mortality were also determined. This paper reports a secondary analysis investigating associations of severe hypoglycaemia with cardiovascular outcomes and mortality.MethodsIn DEVOTE, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 40 publications
(51 reference statements)
8
101
0
14
Order By: Relevance
“…The independent association of HbA1c variability with all‐cause mortality is consistent with a post hoc analysis of the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trial and two previous retrospective studies of limited size, which also found no correlation between HbA1c‐MEAN and mortality after adjusting for HbA1c‐SD or HbA1c‐CV . In addition, our findings are consistent with studies reporting a relationship between visit‐to‐visit (day‐to‐day) variations in fasting glucose and mortality, including the recent Trial Comparing Cardiovascular Safety of Insulin Degludec versus Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) …”
Section: Discussionsupporting
confidence: 91%
“…The independent association of HbA1c variability with all‐cause mortality is consistent with a post hoc analysis of the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trial and two previous retrospective studies of limited size, which also found no correlation between HbA1c‐MEAN and mortality after adjusting for HbA1c‐SD or HbA1c‐CV . In addition, our findings are consistent with studies reporting a relationship between visit‐to‐visit (day‐to‐day) variations in fasting glucose and mortality, including the recent Trial Comparing Cardiovascular Safety of Insulin Degludec versus Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) …”
Section: Discussionsupporting
confidence: 91%
“…However, no association between prior exposure to severe hypoglycemia and stroke was observed . Recently published secondary analysis of the double‐blind Trial Comparing Cardiovascular Safety of Insulin Degludec versus Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) trial also evaluated the association between exposure to severe hypoglycemia and a major adverse cardiovascular event (MACE), defined as either cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke . This study observed an association between exposure to severe hypoglycemia and all‐cause mortality.…”
Section: Incidence Of Hypoglycemia and The Risk Of Cerebrovascular Evmentioning
confidence: 99%
“…Further complicating treatment, patients aged 65 years or older are more susceptible to severe hypoglycaemic events than younger patients, in part because of a reduced ability to recognize and respond to symptoms . Severe hypoglycaemia has been shown to be associated with a higher risk of adverse cardiovascular (CV) events and mortality . In addition, severe hypoglycaemic episodes can increase utilization of healthcare resources .…”
Section: Introductionmentioning
confidence: 99%